VD_FINDINFO Jug / 2016 / 263 vom 4. Februar 2016 - VD Tribunal cantonal (2016)
DÉCISION D'IRRECEVABILITÉ, INDEMNITÉEN GÉNÉRAL, ACTION RÉCURSOIRE, FRAIS DE LA PROCÉDURE | 403 al. 1 let. a CPP (CH), 420 CPP, 427 CPP (CH), 429 al. 1 let. a CPP (CH)